As contribuições: uma análise a partir da regra constitucional de competência da destinação - Silva, Frederico Silveira e (2023)
The object of this work is to analyze the contributions based on the constitutional rules of competence, giving greater emphasis to the rule for the allocation of the proceeds from the collection. We followed the normative and semiotic methods of analysis, initially establishing solid foundations in the General Theory of Law and Philosophy of Law, making considerations about the language of the normative message until it flows into the legal norm as a product of interpretation. Then, we verify the classification of the tributary species, with greater relevance to the study of the pentapartite theory of the tributes, presenting its criteria, and concepts of each one of the five tributary species. Having overcome this step, we unveil the types and subtypes of contributions created based on the Federal Constitution of 1988, segmenting the social, general and social security, interventional, corporate contributions and the contribution to the cost of the public lighting service, overflowing in the analysis of each of the structure rules of these contributions. Once this pre-understanding of the phenomenon has been formulated, it focuses on the study of the completeness of the command of the constitutional rule for the structure of contributions, thus revealing the indissoluble and conditioning union of the rule-matrix of incidence with the rule of destination of the contribution